Phenylketonuria: A Comprehensive Review of Pathophysiology, Diagnosis, and Management Strategies - Agata Konopka; Zuzanna Szczepaniak; Natalia Wdowiak; Dominika Ziółkowska; Kinga Adamska; Karina Lissak (Quality in Sport, 2024)
Introduction: Phenylketonuria (PKU) is a genetically determined congenital metabolic disorder characterized by the body's inability to properly metabolize the amino acid phenylalanine, which is ingested through food. This deficiency leads to the accumulation of phenylalanine in the blood. If untreated, this can result in neurological damage and cognitive impairments. Despite significant progress in understanding the disease, along with advancements in diagnostic methods, the fundamental approach to managing PKU has remained consistent: early detection and adherence to a diet low in phenylalanine are essential to preventing the adverse effects of the disorder.